Gun Violence and Psychopathy Among Female Offenders - Thomson, Nicholas D. (Frontiers in Psychology, 2022)
Research exploring risk factors of gun violence is limited, especially research involving women as perpetrators of violence. Yet, women account for 18-21% of convicted violent crime. The present study aimed to test if psychopathy, a notable risk factor for violence, was related to past convictions of gun violence, general forms of violence, and nonviolent crime. In a sample of 206 female offenders, multinomial logistic regressions assessed how interpersonal, affective, and behavioral psychopathic traits increased the likelihood of women belonging to the gun violence group, a violent crime group, and a nonviolent crime group. Results showed the interpersonal and affective facets increased the likelihood of women belonging to the gun violence group compared to both the violent and nonviolent crime groups. The behavioral facet increased the likelihood of women belonging to the violent crime group when compared to the gun violence and nonviolent crime groups. These results suggest that gun violence has different risk factors than violent and nonviolent crime. This line of inquiry indicates that existing violence prevention strategies may need to be modified to address gun violence.